Repeated Aconitine Treatment Induced the Remodeling of Mitochondrial Function via AMPK–OPA1–ATP5A1 Pathway - Qiu, Li-Zhen; Zhou, Wei; Yue, Lan-Xin; Wang, Yi-Hao; Hao, Fei-Ran; Li, Peng-Yan; Gao, Yue (Frontiers in Pharmacology, 2021)
Aconitine is attracting increasing attention for its unique potential pharmacological effects on the cardiovascular system. However, underlying molecular mechanisms, especially in the context of the positive inotropic effect induced by repeated-dosing of aconitine at low levels, are still not fully understood. The cardiotonic effect always requires abundant energy supplement, which is mainly related to mitochondrial function. And OPA1 has been documented to play a critical role in mitochondrial morphology and energy metabolism in cardiomyocytes. Hence, this study was designed to investigate the possible mechanism involved in the positive inotropic effect caused by repeated aconitine treatment and to further elucidate the potential role of OPA1 in this progress. Our results showed that repeated treatment with low-doses (0-10 μM) of aconitine for 7 days did not induce detectable cytotoxicity and enhanced myocardial contraction in NRVMs. Also, we first identified that 5 μM of aconitine could trigger an obvious perturbation of mitochondrial homeostasis in cardiomyocytes by accelerating mitochondrial fusion, biogenesis, and Parkin-mediated mitophagy, followed by the increase in mitochondrial function and the cellular ATP content, which was identified to be related to the upregulation of ATP synthase α-subunit (ATP5A1). Besides, co-treatment with Compound C, an inhibitor of AMPK, could reverse aconitine-increased the content of phosphor-AMPK, OPA1, and ATP5A1, and the following mitochondrial function. In conclusion, this study first demonstrated that repeated aconitine treatment could cause the remodeling of mitochondrial function via AMPK-OPA1-ATP5A1 pathway, and provide a possible explanation for the cardiotonic or rejuvenation effect induced by aconitine-containing herbs at recommended or lower doses.